Peran Guru dalam Pelaksanaan Evaluasi Pembelajaran di Sekolah - Cendani Alfanizha Hidma; Laudy Livinti; Salisa Afany; Zoe Zarka Syafiq; Muhammad Kurniawan Lubis; Inom Nasution (Universitas Katolik Widya Karya Malang, 2023)
This research is aimed at knowing and analyzing what the teacher's role is in carrying out learning evaluation in schools. This research was carried out using qualitative research using the method of literature study or through literature study, namely collecting information relevant to the topic or problem that is the object of discussion which describes the role of the teacher in the evaluation of learning. The subject of this research is the teacher who plays a role in carrying out the evaluation of learning in schools. The results of this study indicate that in the learning evaluation process, the teacher acts as an evaluator whose function is to find out whether or not a teacher is successful in the learning process, or evaluation can also be said to be a determinant to find out whether the process/method of teaching and learning must be maintained or improved.